Strongly Bipolar Inner Ejecta of the Normal Type IIP Supernova ASASSN-16at - Subhash Bose; Subo Dong; N. Elias-Rosa; B. J. Shappee; David Bersier; Stefano Benetti; M. D. Stritzinger; D. Grupe; C. S. Kochanek; J. L. Prieto; Ping Chen; H. Kuncarayakti; et al. (IOP PUBLISHING LTD, 2022)
We report distinctly double-peaked H alpha and H beta emission lines in the late-time, nebular-phase spectra (greater than or similar to 200 days) of the otherwise normal at early phases (less than or similar to 100 days) type IIP supernova ASASSN-16at (SN 2016X). Such distinctly double-peaked nebular Balmer lines have never been observed for a type II SN. The nebular-phase Balmer emission is driven by the radioactive Co-56 decay, so the observed line profile bifurcation suggests a strong bipolarity in the Ni-56 distribution or in the line-forming region of the inner ejecta. The strongly bifurcated blueshifted and redshifted peaks are separated by similar to 3 x 10(3) km s(-1) and are roughly symmetrically positioned with respect to the host-galaxy rest frame, implying that the inner ejecta are composed of two almost-detached blobs. The red peak progressively weakens relative to the blue peak, and disappears in the 740 days spectrum. One possible reason for the line-ratio evolution is increasing differential extinction from continuous formation of dust within the envelope, which is also supported by the near-infrared flux excess that develops after similar to 100 days.